2020
DOI: 10.1007/s13158-020-00267-3
|View full text |Cite
|
Sign up to set email alerts
|

The Coronavirus Pandemic and Lessons Learned in Preschools in Norway, Sweden and the United States: OMEP Policy Forum

Abstract: The novel coronavirus, also known as COVID-19, has moved rapidly across the world in 2020. This article reports on the recent consequences of the pandemic for early childhood education in Sweden, Norway, and the United States. The authors illustrate the effects of the pandemic on preschools in their countries, against a backdrop of frequent changes in infection and mortality rates, epidemiological understandings, government strategies, and mitigation strategies regarding preschool closures. Teachers report the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 4 publications
5
49
0
15
Order By: Relevance
“…An emphasis on play among parents in Ireland was also reported by Egan and her colleagues (Egan, Chloe Beatty, and Hoyne 2020) who found that up to 78% of over 500 parents, of children aged one to ten years, reported an increase in time spent engaging in outdoor play, play with games and toys as well as on-screen activities in comparison to before the pandemic. Cross-cultural findings reported by Samuelsson, Wagner, and Ødegaard (2020) across three ECE centers in Sweden, Norway and the US indicate the incorporation of dramatic play activities as part of remote schooling as well as the provision of activities and resources for parents. However, limited data is currently available on play in the context of educational plans for supporting young children during school closures and when schools reopen.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An emphasis on play among parents in Ireland was also reported by Egan and her colleagues (Egan, Chloe Beatty, and Hoyne 2020) who found that up to 78% of over 500 parents, of children aged one to ten years, reported an increase in time spent engaging in outdoor play, play with games and toys as well as on-screen activities in comparison to before the pandemic. Cross-cultural findings reported by Samuelsson, Wagner, and Ødegaard (2020) across three ECE centers in Sweden, Norway and the US indicate the incorporation of dramatic play activities as part of remote schooling as well as the provision of activities and resources for parents. However, limited data is currently available on play in the context of educational plans for supporting young children during school closures and when schools reopen.…”
Section: Discussionmentioning
confidence: 96%
“…Such concerns were further compounded by a reported lack of support and guidance which may further impact teachers' capacity to incorporate play into classroom practice. This sense of apprehension is reflected throughout national and international research literature, in which teachers have expressed significant concerns regarding a lack of clarity and guidance in planning their return to the classroom following school closures (Dempsey and Burke 2020;Eivers, Worth, and Ghosh 2020;Samuelsson, Wagner, and Ødegaard 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study is critical because there is little published research examining the effects of the Covid-19 pandemic on preschool education (Massachusetts Office of the Child Advocate 2020 ; Pramling Samuelsson et al 2020 ). Therefore, we believe that this study will pave the way for further research.…”
Section: Introductionmentioning
confidence: 99%
“…Bentuk pembelajaran dapat dikemas seperti melakukan pembelajaran secara online dengan memanfaatkan aplikasi seperti zoom meeting, whatsapp, dan Microsoft team, guru memberikan tugas yang harus dikerjakan anak di rumah, memberikan modul sebagai panduan bagi orang tua dalam membimbing anak melakukan kunjungan ke rumah anak, dan guru juga melakukan tatap muka berkelompok dengan tetap mematuhi protocol kesehatan. Hasil temuan penelitian (Pramling Samuelsson et al, 2020) guru membuat buku pegangan digital, menyampaikan pemberitahuan melalaui website dan aplikasi online, membuat video pembelajaran seperti menyanyi dan membaca cerita. Selain pembelajaran melalui aplikasi kunjungan ke rumah anak juga merupakan salah satu alternatif yang dilakukan oleh guru agar anak tetap merasa dekat dengan guru dan tidak jenuh dengan pembelajaran yang dilakukan secara daring atau online.…”
Section: Strategi Guruunclassified